Probing of biofilms on copper under anoxic conditions considering corrosion processes - Kilkku, Katariina (My University, 2024)
Copper is the chosen material in the canister of spent nuclear fuel storage in Finland. The canister is placed in bedrock and surrounded with bentonite clay, which should prevent the flow of microbes from the groundwater to the copper surface. If the microbes come in contact with the canister, they can attach and form biofilms and may cause microbially influenced corrosion. Biofilms can be studied using microsensors, which offer high spatial resolution with minimal disturbance of the sample. The aim of this study was to introduce the use of microsensors for studying of copper corrosion occurring under biofilms in anoxic conditions. An artificial biofilm matrix was prepared and tested with microsensors using chemical gradients where relevant analytes were used to make gels with known concentrations layered on top of each other. The matrix was mixed with microbial solutions to produce different microbial biofilms for an aerobic and an anaerobic experiment and casted on top of copper coupons. A control biofilm of only the matrix was prepared for both. The anaerobic experiment was performed inside an anaerobic chamber. The biofilms were studied using O2, H2S, redox and pH microsensors three times over two weeks. The surfaces of the copper coupons were studied photographically. The chemical gradient experiment proved the artificial biofilm matrix to be suitable for use as it did not alter the expected results. The microsensors measurements indicated microbial activity in all microbial biofilms but no corrosive environments were detected. The results of the anaerobic experiment were inconclusive as increasing H2S concentration indicated the activity of anaerobic microbes, but the redox potential of the environment revealed unsuitable conditions for the activity. The surface analysis showed severe changes under the aerobic microbial biofilms, but no noticeable corrosion was seen under the anaerobic biofilms. The study revealed differences between the microbial biofilms but not all results were compatible with microbial activity. The use of microsensors in an anaerobic chamber proved to be challenging. While the microsensors can be used to study corrosive environments they should be used together with surface analysis methods that recognize corrosive substances.

Kuparia käytetään Suomessa ydinjätteen loppusijoituksen kanistereissa. Kanisterit sijoitetaan peruskallioon ja ympäröidään bentoniittisavella, jonka tarkoituksena on estää pohjavedessä olevien mikrobien pääsy kanisterin pinnalle. Kuparin pinnalle päästyään mikrobit voivat muodostaa biofilmejä ja saattavat aiheuttaa mikrobiologista korroosiota. Biofilmejä voidaan tutkia mikrosensoreilla, jotka mahdollistavat ympäristön tarkan mittauksen näytettä vahingoittamatta. Tämän tutkimuksen tarkoituksena oli ottaa käyttöön mikrosensoriteknologia kuparin korroosion tutkimiseen biofilmien alla hapettomissa olosuhteissa. Tutkimuksessa valmistettiin keinotekoinen biofilmimatriisi, jonka käyttöä tutkittiin valmistamalla matriisista geelejä, joissa oli mikrosensoreilla mitattavia analyyttejä tunnetuissa pitoisuuksissa. Geelejä kerrostettiin päällekkäin kemiallisiksi gradienteiksi. Biofilmimatriisista valmistettiin biofilmejä sekoittamalla niihin mikrobeja hapelliseen ja hapettomaan kokeeseen. Biofilmit valettiin kuparinäytteiden pinnalle, ja lisäksi kumpaankin kokeeseen valmistettiin kontrollibiofilmi pelkästä matriisista. Hapeton koe tehtiin anaerobikaapissa. Biofilmejä tutkittiin happi-, sulfidi-, hapetus-pelkistyspotentiaali- ja pH-mikrosensoreilla kolmesti kahden viikon ajan. Kuparien pintoja analysoitiin valokuvien avulla. Keinotekoinen biofilmimatriisi todettiin toimivaksi, sillä se ei merkittävästi muuttanut analyyttien odotettuja pitoisuuksia kemiallisissa gradienteissa. Mikrosensorimittaukset osoittivat mikrobien aktiivisuuden kaikissa mikrobibiofilmeissä, mutta korroosiota aiheuttavia ympäristöjä ei havaittu. Hapettomassa kokeessa kasvava sulfidipitoisuus indikoi mikrobien aktiivisuutta mutta hapetus-pelkistyspotentiaalin perusteella ympäristö oli sopimaton hapettomien mikrobien aktiivisuuteen. Pinta-analyysissä hapellisten mikrobibiofilmien alta paljastui merkittäviä muutoksia kuparin pinnalla, mutta hapettomien biofilmien alta merkittävää korroosiota ei havaittu. Tutkimus paljasti eroja mikrobibiofilmien välillä, vaikka kaikki tulokset eivät viitanneet mikrobien aktiivisuuteen. Mikrosensorien käyttö anaerobikaapissa osoittautui hankalaksi. Mikrosensoreja voidaan käyttää korroosiota aiheuttavien ympäristöjen tutkimiseen, mutta niitä tulisi käyttää yhdessä sellaisten pinta-analyysimenetelmien kanssa, joilla pystytään tunnistamaan korroosiotuotteita.
Keywords: biofilm, copper, microbially influenced corrosion, MIC, microsensor, nuclear waste disposal